Indeks Masa Tubuh Dan Lingkar Pinggang Dengan Risiko Obstructive Sleep Apnea Pada Pasien Diabetes Mellitus - Hapipah Hapipah; Nurfadila Nurfadila; Istianah Istianah; Supriyadi Supriyadi (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Diabetes mellitus (DM) is a disease that continues to increase every year and is one of the world's death threats. The triad of DM symptoms includes drinking, eating and urinating frequently as well as drastic weight loss which causes a decrease in body muscle mass in the nasopharynx and oropharynx resulting in collapse and Obstructive sleep apnea (OSA). This study aims to analyze the relationship between body mass index and waist circumference with the risk of obstructive sleep apnea (OSA) in diabetes mellitus patients in the working area of ​​the Karang Pule Health Center, Mataram City. This study uses a correlation research design. The number of samples used was 87 respondents with a purposive sampling technique. Data analysis in this study used the Spearman rank test. The results showed that there was a relationship between body mass index and the risk of obstructive sleep apnea (OSA) in diabetes mellitus patients with a p value of 0.043 (< α 0.05) and there was a relationship between waist circumference and the risk of obstructive sleep apnea (OSA) with a p value of 0.028 (< α 0.05). Based on the results of this study, it is necessary to support the family and diabetics themselves to maintain a good and regular lifestyle and diet in accordance with the 7 pillars of management of diabetes mellitus to prevent various complications.